2015
DOI: 10.4238/2015.december.23.19
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased expression of tumor suppressive miR-874 and its clinical significance in human osteosarcoma

Abstract: ABSTRACT. Dysregulation of microRNAs (miRs) is associated with cancer development and progression and aberrant expression of miR-874 have been found in some types of cancer. However, the expression and function of miR-874 in osteosarcoma remain unclear. The aim of this study was to explore the effects of miR-874 in osteosarcoma tumorigenesis and development. The expression level of miR-874 was quantified by real-time reverse transcription-polymerase chain reaction (RT-PCR) in human osteosarcoma cell lines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Recently, several reports show that miRNA-874 (miR-874) expression is downregulated and functions as a tumor suppressor in several cancers, including non-small cell lung cancer (NSCLC) [ 9 ], breast cancer [ 10 ], osteosarcoma [ 11 , 12 ], gastric cancer [ 13 , 14 ], colorectal cancer [ 15 ], testis cancer [ 16 ], and maxillary sinus squamous cell carcinoma [ 17 ]. Moreover, miR-874 is significantly downregulated in breast cancer cells and its overexpression could suppress growth, colony formation and cycle of breast cancer cells and increase cell apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports show that miRNA-874 (miR-874) expression is downregulated and functions as a tumor suppressor in several cancers, including non-small cell lung cancer (NSCLC) [ 9 ], breast cancer [ 10 ], osteosarcoma [ 11 , 12 ], gastric cancer [ 13 , 14 ], colorectal cancer [ 15 ], testis cancer [ 16 ], and maxillary sinus squamous cell carcinoma [ 17 ]. Moreover, miR-874 is significantly downregulated in breast cancer cells and its overexpression could suppress growth, colony formation and cycle of breast cancer cells and increase cell apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that miR-874 was downregulated in osteosarcoma and inhibits osteosarcoma cell proliferation and metastasis ( 14 ). Therefore, it was speculated that the specific genes suppressed by miR-874 may predominantly function in this process.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that miR-874 inhibited osteosarcoma progression ( 14 ). Therefore, the present study aimed to determine whether miR-874 promotes the proliferation of osteosarcoma cells by targeting CDK9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of miR-874-3p has been reported to be implicated in several disorders, including intestinal barrier dysfunction, skeletal anabolism, allergic rhinitis, asthma, myogenesis and cognitive impairment ( 62 68 ), as well as in the progression and metastasis of several malignancies, such as osteosarcoma, breast, gastric and lung cancer, and head and neck squamous cell carcinoma ( 69 76 ). Furthermore, emerging evidence indicates that miR-874-3p is downregulated in CRC and upregulation of miR-874-3p inhibits growth, induces apoptosis and reverses chemoresistance in CRC ( 77 – 79 ).…”
Section: Discussionmentioning
confidence: 99%